2020
DOI: 10.1097/sle.0000000000000866
|View full text |Cite
|
Sign up to set email alerts
|

Should Sleeve Gastrectomy Be Considered Only as a First Step in Super Obese Patients? 5-Year Results From a Single Center

Abstract: Purpose: Sleeve gastrectomy (SG) has been originally conceived as a first step procedure for super obese (SO) patients, but it is currently considered a stand-alone intervention. Medium-term to long-term studies have shown weight regain and risk of de novo gastroesophageal reflux (GERD). The aim of this study was to evaluate outcomes of SG in SO subjects. Materials and Methods:A retrospective analysis of a prospectively maintained database was carried out to find all SO patients who had undergone SG with a min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Standard technique for LSG has been previously reported [15][16][17]: a five trocars approach (3 × 12 mm, 2 × 5 mm) was used. The gastrectomy started 2-4 cm from the initial weight − final weight∕initial weight × 100.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Standard technique for LSG has been previously reported [15][16][17]: a five trocars approach (3 × 12 mm, 2 × 5 mm) was used. The gastrectomy started 2-4 cm from the initial weight − final weight∕initial weight × 100.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Several bariatric procedures have been proposed to treat severe obesity with BMI > 50 kg/m 2 , including Roux-en-Y gastric bypass (RYGB), one anastomosis gastric bypass (OAGB), single anastomosis duodeno-ileal bypass (SADI), sleeve gastrectomy (SG), and biliopancreatic diversion with duodenal switch (BPD-DS) [8][9][10][11][12][13][14][15]. There is still no robust evidence supporting the choice of one procedure over the others.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that SG is a safe and effective one-stage procedure for patients with BMIs over 50 kg/m 2 [30,31]. However, other studies have reported that SG results in insufficient weight loss in these patients and should only be used as first-stage operation of a 2-stage gastric bypass or BPD/DS [32][33][34][35][36]. Thereaux et al concluded that SG can be an independent factor for weight loss failure in patients with BMIs over 50 kg/m 2 [37].…”
Section: Discussionmentioning
confidence: 99%